Diatom-inspired 2D nitric oxide releasing anti-infective porous nanofrustules - Lim, Hong Kit (2022)
Two-dimensional (2D) nanomaterials (NM) have emerged as promising platforms for antibacterial applications. However, the inherent “flatness” of 2D NM often limits the loading of antimicrobial components needed for synergistic bactericidal actions. Here, inspired by the highly ornamented siliceous frustules of diatoms, we prepared 2D ultrathin (<20 nm) and rigid “nanofrustule” plates via the out-of-plane growth of cetyltrimethylammonium bromide (CTAB) directed silica mesostructures on the surfaces of 2D graphene oxide nanosheets. The nanofrustules were characterized by the presence of mesoporous channels with a pore size of 3 nm and a high specific surface area of 674 m2 g−1. S-nitrosothiol-modification on the silica surfaces enables the development of a novel anti-infective nitric oxide (NO) releasing NO-nanofrustule system. The cage-like mesoporous silica architecture enabled a controlled and sustainable release of NO from the NO-nanofrustules under physiological conditions. The NO-nanofrustules displayed broad antibacterial effects against Staphylococcus aureus and Escherichia coli with a minimum inhibitory concentration of 250 μg ml−1. Mechanistic studies revealed that the antibacterial property of NO-nanofrustules was attained via a unique “capture-and-release” mode-of-action. The first step entailed the capture of the bacteria by the NO-nanofrustules to form micro-aggregates. This was followed by the release of high levels of NO to the captured bacteria to elicit a potent anti-infective effect. In combination with the lack of cytotoxicity in human dermal cells, the 2D hybrid NO-nanofrustules may be utilized to combat wound infections in clinical settings.